Sensory Evaluation of Food - Lawless, Harry T.; Heymann, Hildegarde (Springer, 2010)
The field of sensory science has grown exponentially since the publication of the previous version of this work. Fifteen years ago the journal Food Quality and Preference was fairly new. Now it holds an eminent position as a venue for research on sensory test methods (among many other topics). Hundreds of articles relevant to sensory testing have appeared in that and in other journals such as the Journal of Sensory Studies. Knowledge of the intricate cellular processes in chemoreception, as well as their genetic basis, has undergone nothing less than a revolution, culminating in the award of the Nobel Prize to Buck and Axel in 2004 for their discovery of the olfactory receptor gene super family. Advances in statistical methodology have accelerated as well. Sensometrics meetings are now vigorous and well-attended annual events. Ideas like Thurstonian modeling were not widely embraced 15 years ago, but now seem to be part of the everyday thought process of many sensory scientists. And yet, some things stay the same. Sensory testing will always involve human participants. Humans are tough measuring instruments to work with. They come with varying degrees of acumen, training, experiences, differing genetic equipment, sensory capabilities, and of course, different preferences. Human foibles and their associated error variance will continue to place a limitation on sensory tests and actionable results. Reducing, controlling, partitioning, and explaining error variance are all at the heart of good test methods and practices. Understanding the product– person interface will always be the goal of sensory science. No amount of elaborate statistical maneuvering will save a bad study or render the results somehow useful and valid. Although methods continue to evolve, appreciation of the core principles of the field is the key to effective application of sensory test methods. The notion that one can write a book that is both comprehensive and suitable as an introductory text was a daunting challenge for us. Some may say that we missed the mark on this or that topic, that it was either too superficially treated or too in depth for their students. Perhaps we have tried to do the impossible. Nonetheless the demand for a comprehensive text that would serve as a resource for practitioners is demonstrated by the success of the first edition. Its widespread adoption as a university level text shows that many instructors felt that it could be used appropriately for a first course in sensory evaluation.
Principles and Practices